Evans syndrome after unrelated bone marrow transplantation for refractory cytopenia of childhood. (29th July 2014) - Ueki, Hideaki; Igarashi, Shunji; Kimura, Shunsuke; Tsuchimochi, Taichiro; Furudate, Kazuki; Sakurai, Ayako; Noguchi, Yasushi; Sunami, Shosuke
Abstract Post‐transplant ES, which is often resistant to therapies, has seldom been described. This report describes a case of ES after UBMT for RCC. A five‐yr‐old boy developed RCC with no evidence of monosomy 7. Because no matching family donors were available for SCT and immunosuppressive therapy was ineffective, UBMT was performed when he was six yr old. The conditioning regimen included TAI (3 Gy) and administration of FLU, CY, and rabbit antithymocyte globulin. The recovery of blood cells was good. He displayed grade II acute GVHD involving only the skin. ES developed on day 66, with positive results for Epstein–Barr virus DNA and HHV 6. Cytopenia was resolved with treatment with RTX, GCV, an escalated dose of steroids, high‐dose gammaglobulin, and romiplostim. No relapse has occurred since discontinuing steroids on day 177 and romiplostim on day 268. Post‐SCT ES after UBMT is rare, and the risk factors and therapies are unclear. Prospective analysis and collection of cases from multiple centers are required for clarification.